Effects of Humic Acids, Seaweed Extract and Equisetum arvense L. Extracts on Morphological, Histological and Physiological Parameters of the Ornamental Plant Ocimum basilicum Rokokó - Szilvia Kisvarga; Katalin Horotán; Dóra Hamar-Farkas; László Orlóci (Horticulturae)
Ocimum basilicum L. is a multipurpose plant species used in the horticultural sector as a medicinal, herbaceous and ornamental plant. In our experiment, the Hungarian cultivar O. basilicum Rokokó was treated with algae (Ecklonia maxima (Osbeck) Papenf.), horsetail (Equisetum arvense L.) extracts and humic extracts. The effect of the biostimulants on the groups was assessed by morphological (leaf number, leaf area, fresh green mass, fresh root mass), histological (number of volatile oil glands) and physiological (chlorophyll content, peroxidase enzyme activity, proline levels) measurements. Obtained results were evaluated and it was concluded that the plants treated with algae and E. arvense extracts showed remarkable results for all the parameters measured. It was concluded that these extracts can be used as biostimulants in the cultivation of basil seedlings as ornamental plants, as they have a beneficial effect on the development of the plant. The humic extracts were less effective during the time period studied, probably due to their high molecular weight, which would have resulted in a longer absorption time. For the humic extracts, foliar application was less effective than irrigation, probably due to rapid damping-off, which reduced the penetration of humic extracts into the leaves. Though morphological characteristics are especially important for basil used as an ornamental plant, the plant’s essential oil content can also be important in attracting attention in urban plantings. It was found that humic extracts applied (22.8 pcs/sampling area) with irrigation had a strong effect on essential oil glands, in contrast when used as a spray (13.1 pcs/sampling area). The lowest stress levels were obtained in the group treated with irrigated humus extracts (274.96 µg/mg), which may be related to the continuous supply of nutrients, and in the group treated with E. arvense extract, silicon (219.05 µg/mg) may be the result of hermetic effects. In conclusion, E. arvense and algae extracts can be effective biostimulants in the horticultural sector for the seedling production of ornamental basil, and after a longer growing period, humic extracts can be used effectively by irrigation after planting. The use of natural extracts can also give a green light to this segment for sustainable and environmentally friendly cultivation, which can also better resist the effects of climate change and urbanisation.